Beyond Grades: Investigating the Influence of Personality on STEM Pathways in Malaysia - Rashidin Idris; Priyalatha Govindasamy; Suppiah Nachiappan; Juppri Bacotang (ResearchGate, 2023)
The influence of personality on STEM (Science, Technology, Engineering, and Mathematics) education interest and job choices among Malaysian secondary school students is a developing concern in the educational sector. The purpose of this study is to look at the relationship between personality traits and STEM education desire in Malaysia. The study discovered significant relationships between personality qualities such as openness to experience, agreeableness, and extraversion with student interest in STEM education. These findings shed light on how personality factors influence STEM education enthusiasm among Malaysian secondary school students, where enrolment is now falling. The implications of these findings for educators, policymakers, and stakeholders interested in encouraging secondary school students' interest in STEM education and career options are examined. More research is needed to better understand the complex relationship between personality and STEM education interest, as well as to inform strategies for increasing secondary school students' interest and involvement in STEM fields in Malaysia and elsewhere.